Avaliação da hiperplasia tímica durante infecção aguda por Leishmania amazonensis em modelo murino - Reis, Karen Almeida (2021)
In this work, the possible cause of thymic hyperplasia during the acute phase of L. amazonensis infection was verified. We used 20 isogenic mice of the BALB/c lineage, females aged between 6 and 8 weeks, divided into 4 groups: control, 3rd, 5th and 10th day after infection, inoculated with a concentration of 106 amastigotes of the parasite, passed the days of infection, the animals were euthanized and the thymus removed for histological, immunohistochemical, and western blotting analyses. On the 5th day after infection, the thymic index was higher than that of control animals (0.31±0.0067 vs 0.39±0.040 g/kg- mouse), and the area of the cortical region became larger (15, 49±4.80 vs 7.79±1.33 mm2), with a decrease in the medullary region (2.66±2.15 vs 5.69±1.58 mm2). In addition, the expression of the cell proliferation marker Ki67 was high on the 3rd and 5th days of infection (% 11.23±4.71 vs 25.10±5.51 vs 27.59±4.75) the elevation occurred mainly in the cortical region of the thymus, where cells are concentrated in the initial stage of maturation, whereas the concentration of type 1 receptor for Sphingosine-1-phosphate (S1P1), related to the migration of T cells to the lymphoid organs secondary (0.96±0.10 vs 1.88±0.16 AU), was higher in the vascular region of the thymic medulla. We conclude that thymic hyperplasia may be caused by an increase in the proliferation of thymic cells at the beginning of the maturation process and, probably, by the retention of mature T cells, due to an alteration in migration factors, in the acute phase of the infection, the that could alter the peripheral response against the parasite and the establishment of chronic infection.